Evidence-Based Practice Competency of Registered Nurses in the Greek National Health Service - Stefania Schetaki; Evridiki Patelarou; Konstantinos Giakoumidakis; Christos Kleisiaris; Athina Patelarou (MDPI AG, 2023)
Nurses' competency toward evidence-based practice (EBP) has been extensively investigated by several studies worldwide. However, factors affecting the competence of Greek nurses working in the NHS have not been fully investigated in terms of EBP. Thus, this study aimed to explore the impact of the individual qualifications of nurses on their competence toward EBP. Data from 473 registered nurses working in 10 hospitals in the Greek National Health Service (NHS) were collected between October and December 2020 using a convenience sampling method in a cross-section design. The Greek version of the 35-item (five-point Likert scale) Evidence-Based Practice Competency Questionnaire for Professional Registered Nurses (EBP-COQ Prof) was used to assess the competence level of nurses, focusing on attitudes, skills, and knowledge, as well as the utilization of EBP in clinical practice. One-way ANOVA and Pearson coefficient tests were applied to compare the possible differences among variables (two or more groups) as appropriate. A multi-factorial regression model was applied to explore participants' qualifications, including demographics (MSc degree, gender, English language knowledge, etc.) as independent variables, and to control for potential confounding effects toward EBP competency. The p-values < 0.05 were considered statistically significant. The mean age of the 473 participants (402 women and 71 men) was 44.7 ± 9.2 years old. The mean value of competence subscales was found as follows: attitudes 3.9 ± 0.6, knowledge 3.7 ± 0.6, skills 3.1 ± 0.8, and utilization 3.4 ± 0.7. A multivariate regression analysis revealed that associates of "Master's degree" (t = 3.039, p = 0.003), "Writing an academic article" (3.409, p = 0.001), "Working in a University clinic" (2.203, p = 0.028), and "Computer Skills" (2.404, p = 0.017) positively affected "Attitudes", "Knowledge", "Skills", and "Utilization", respectively. The research data suggest that nurses working in the Greek NHS were limited in competence regarding EBP in comparison with other European countries. Therefore, vocational, educational, and training programs tailored to EBP enhancement are crucially important. This study was not registered.